ANALISIS KEPUASAN PELANGGAN DAN KUALITAS PELAYANAN PADA PENGGUNA TRANSPORTASI ONLINE MAXIM - Liana, Liana; Yinna, Yinna; Chen, Michael; Rahmah, Fany (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2024)
This research aims to determine customer satisfaction and the quality of consumer service when using online transportation service application, Maxim. This research is quantitative research by conducting a survey using a questionnaire research instrument. The data used is primary data obtained by distributing questionnaires online to Maxim users in the city of Medan using accidental sampling techniques to 30 respondents. The research results show that the majority of respondents are satisfied with Maxim's services. Most respondents felt their hopes and desires were met, would not hesitate to use Maxim again, and were willing to recommend it to others. Respondents also assessed that Maxim was quite punctual, safe and used a suitable vehicle.